FISCAL POLICY AND THE DIGITALIZATION OF TAX ADMINISTRATION - Babayeva Sabinabonu Davronbek qizi (Ecomind Press, 2025)
Digitalization is becoming a strategic direction in the transformation of fiscal policy, enhancing its efficiency, transparency, and sustainability. This article examines the impact of digital technologies on tax administration, analyzing international case studies using examples from countries such as Estonia, South Korea, and Brazil. It also proposes pathways for further development. Special attention is given to digital platforms, artificial intelligence systems, and big data processing. The findings of the study confirm the high importance of digitalization in ensuring the sustainability of public finances in the 21st century.
Keywords: Fiscal policy, digitalization, tax administration, artificial intelligence, big data, international experience.